Effects of NGF Addition on Llama (Lama glama) Sperm Traits After Cooling - Sari, Luciana María (2021)
To provide new insights into the mechanisms through which seminal plasma proteins can protect sperm from damage caused during refrigeration, we evaluate the possibility that β-NGF can contribute to the improvement of sperm quality after cooling. First, β-NGF was detected in refrigerated sperm and compared with unrefrigerated sperm by western blotting of the proteins adsorbed by sperm, showing that native β-NGF is still present even 24 h after cooling only as an active form. Then, the effect of exogenous β-NGF on sperm quality after cooling was evaluated. A total of 12 ejaculates from male llamas (three ejaculates per male), were obtained by electro-ejaculation, diluted 4:1 with buffer Hepes-balanced salt solution and centrifuged at 800 × g for 8 min to remove the seminal plasma. Sperm were suspended in Tris-citrate-fructose-egg yolk diluent for a final concentration of 30 ×106/ml and cooled at 5°C for 24 h. After refrigeration, the extended sperm were equilibrated for 5 min at 37°C and divided into the following subgroups: sperm samples without treatment (control) and sperm samples supplemented with exogenous human β-NGF (10, 100, and 500 ng/ml). At 5, 30, and 60 min of incubation sperm were evaluated for sperm viability (using eosin/nigrosin stain), sperm motility and vigor (observed under light microscopy), and mitochondrial activity (using the JC-1 fluorescent marker). Vigor data were analyzed with the nonparametric Kruskal-Wallis test. The rest of the variables were analyzed with a mixed models approach. Mean comparisons were performed using Fisher's LSD test with a confidence level of 95%. A principal components analysis was performed to analyze the relationships between variables. Treatment of 24 h cooled sperm with 10 or 100 ng/ml of human β-NGF increased the percentage of total motility and vigor (p < 0.05). Besides, an incubation time of 60 min would be adequate to improve sperm quality, since all variables are positively related. The significant improvement observed in the motility and vigor of post-refrigerated sperm suggests that supplementation with exogenous β-NGF may be profitable for the improvement of cooled llama sperm.